Overexpression of LVRN impedes the invasion of trophoblasts by inhibiting epithelial–mesenchymal transition. (23rd December 2020) - Feng, Xuan; Wei, Zhi; Zhang, Sai; Zhou, Jiayi; Wu, Jing; Luan, Baoxin; Du, Yan; Zhao, Hongbo
Abstract: Laeverin (LVRN) was first detected on the outer layer of the chorion laeve and migrating extravillous trophoblasts (EVTs). It is an enzyme that plays an important role in the placentation and pathophysiology of preeclampsia (PE). Previous studies have indicated that LVRN may be required for the invasion of human trophoblast cells. Paradoxically, LVRN was found to be highly expressed in the trophoblasts of PE patients with impaired invasive capacities. In this study, we detected the expression of LVRN in the placentas of PE patients ( n =5) and normal term pregnancy women ( n =5) as a control group by immunohistochemistry. LVRN was elevated in decidua ( P =0.0083) and villi ( P =0.0079) of PE patients. Next, LVRN was overexpressed via adeno-associated virus-mediated gene transfer in trophoblastic cell lines HTR8, Swan71, and JAR. Matrigel transwell assay and wound healing assay showed that overexpression of LVRN impeded the invasion of these three cell lines. Western blot analysis showed that LVRN overexpression caused downregulation of N-cadherin and vimentin and upregulation of E-cadherin, suggesting the inhibitory role of LVRN in epithelial–mesenchymal transition (EMT). Moreover, our data indicated that long noncoding RNA NONSTAT103348 ( lnc10-7 ) was elevated in PE patients. Silencing lnc10-7 led to decreased LVRN expression. Taken together, although the basal level of LVRN may be crucial for cell invasion, overexpression of LVRN may abrogate the cell invasiveness, suggesting a multifaceted role of LVRN in the pathogenesis of PE.